Polityka z historią w tle. Trudne dziedzictwo w relacjach polsko-ukraińskich w latach 1991-2015 - Mróz, Maciej (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2015)
Polish-Ukrainian relations in 1991–2015 were significantly determined by difficult historical legacy, and its impact on the policies of the consecutive governments in both countries after 1991 seems to be of a multifaceted nature. One may be temptedto formulate a thesis related to crucial significance of historical determinants and difficult topics as well as their influence on mutual relations. Undoubtedly, it was Poland who would usually initiate the trial of mutual relations. Polish political elites, which usually could not get rid of wording espressing dramatic historical experience, demonstrated excessive tendency to think about the Ukrainian issue in terms of ad hoc actions rather than in terms of a long-term perspective. As for the Ukrainian part, the debate over common tragic history, especially in the 20th century, turned out to be an extremely difficult challenge. Stereotypes and historical resentments turned out to be an extremely difficult component to overcome in Polish-Ukrainian relations at the turn of the 21st century.
Keywords: Polska; Ukraina; Unia Europejska; NATO; strategiczne partnerstwo; trudne dziedzictwo; stereotypy